(untitled) (Journal of Engineering, 2025)
This paper investigates the potential enhancement of the seismic performance of reinforced concrete square columns by modifying their geometry from prismatic to non-prismatic, while maintaining the same volume. Two one-bay by two-bay three-story RC frames were simulated using ABAQUS software; the first has prismatic columns serving as the reference model, and the second has non-prismatic columns. Static lateral loads were applied to both frames after the application of gravity loads. Additionally, two one-bay by one-bay six-story RC buildings were modeled in ABAQUS; one has prismatic columns and the other has non-prismatic columns. These two models were subjected to the El Centro 0.32g NS 1940 earthquake, and time-history analyses were performed. The results showed that the seismic response, in terms of base shear capacity and stiffness, was significantly improved in the case of columns linearly tapered from a smaller cross-section at mid-height to a larger cross-section at the ends. For a tapering angle of 3.814°, the lateral strength increased by 56.4%, and the initial stiffness improved by 50.5%. Moreover, the overstrength factor of the RC frame with tapered columns increased by 56.48% compared to the prismatic-column reference model. The damage pattern in the frame with non-prismatic columns was also more favorable than that of the reference frame.